Origins of Latin American inequality - Francisco Eslava; Felipe Valencia Caicedo (Inter-American Development Bank (IDB), 2023)
How deep are the roots of Latin America's economic inequalities? In this chapter we survey both the history and the literature about the region's extreme economic disparities, focusing on the most recent academic contributions. We begin by documenting the broad patterns of national and sub-national differences in income and inequality, building on the seminal contributions of Engerman and Sokoloff (2000; 2002, 2005) and aiming to capture different dimensions of inequality. We then proceed thematically, providing empirical evidence and summarizing the key recent studies on colonial institutions, slavery, land reform, education and the role of elites. Finally, we conduct a "replication" exercise with some seminal papers in the literature, extending their economic results to include different measures of inequality as outcomes.
Keywords: D02; D63; I24; N10; N16; O43; Q15; 330; Inequality; Latin America; History; Colonization; Persistence; Slavery; Land Reform; Education; Elites